Senegal dairy genetics: Improved food and nutritional security from better breeds in Senegal - International Livestock Research Institute (International Livestock Research Institute, 2014)
This photo-film shows the main activities Senegal Dairy Genetics project (http://senegaldairy.wordpress.com/) which seeks to improve food and nutrition security in Senegal through better utilization of dairy cattle breed-types. The project is funded via the Finnish Government's FoodAfrica Program.